2021
DOI: 10.1111/jcpe.13439
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profiles of oral soft tissue‐derived fibroblast from healing wounds: correlation with clinical outcome, autophagy activation and fibrotic markers expression

Abstract: Wound healing is a complex process orchestrated by a variety of known and unknown factors, divided into four stages (haemostasis, inflammation, proliferation and remodelling) that occur in both skin and oral tissues (Hämmerle & Giannobile, 2014). However, oral tissues present special features as rapid wound closure and reduced scar formation (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 46 publications
5
11
0
Order By: Relevance
“…In our previous studies [28,29], we demonstrated a downregulation of αSMA and Col1a1 in gingival tissue 24 h after injury, in line with clinical observation of reduced scar formation in this tissue. Instead of this, the alveolar mucosal (M) tissue showed the opposite response, according to the clinical observation of scar tissue repair.…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…In our previous studies [28,29], we demonstrated a downregulation of αSMA and Col1a1 in gingival tissue 24 h after injury, in line with clinical observation of reduced scar formation in this tissue. Instead of this, the alveolar mucosal (M) tissue showed the opposite response, according to the clinical observation of scar tissue repair.…”
Section: Discussionsupporting
confidence: 86%
“…The other two genes that play a role in regulating scar formation in oral tissues, SERPINE1 and TIMP1, were evaluated. Such genes, involved in collagen deposition and fibrosis, were previously shown to remain stable in gingival tissue at 24 h after injury [29]. In our study, we observed an increase of SERPINE1 and TIMP1 in CHX biopsies of both patients (1.6 and 3.0-fold for SERPINE1; 3.4 and 11.8-fold for TIMP1, respectively; Figure 3B,C).…”
Section: Chx Influences the Expression Of Key Genes Involved In Early Wound Healingsupporting
confidence: 77%
See 3 more Smart Citations